EVALUASI PENERAPAN PERPUSTAKAAN DIGITAL PADA PERGURUAN TINGGI MENGGUNAKAN PENDEKATAN ITPOSMO - Lusino, Lusino (EDUTECH CONSULTANT, 2019)
Many aspects need to be considered in evaluating digital libraries. The rapid development of information and communications technology will change the model and pattern of libraries . Referring to this, encourage the libraries to look for alternative library system to change the culture of conventional library into a digital library. The most important thing in the implementation of this system is to be successful or successful in its implementation. One indicator of success is if the effective e-Library. Therefore, it is necessary to study what gaps that exist in the application of digital libraries. According to Richard Heeks there are seven dimensions that need to be analyzed: (1) Information gap (2) Technology gap (3) Process gap (4) Object and Value gap (5) Staff and Skill gap (6) Management and Structure gap (7) Others Resourcess gap or abbreviated ITPOSMO. The samples in this research using questionnaires filled out by 270 respondents consisting of two universities, namely University of Jakarta as much as 145 respondents and the School of Information Management (STMIK MIC) of 125 respondents. Data processing method using the average by using the software SPSS 17. The results showed that there are gaps in the application of digital libraries in both college although not too wide gap that exists. However, based on seven dimensions IPOSMO the application of digital libraries in colleges partial failure.